Cerebrospinal fluid rhinorrhea: a novel approach - Mohanty, Deeganta; Kumar, P. Sunil; Sahithi, Konda (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: This study aimed to describe the use of nasal endoscopic technique in the management of cerebrospinal fluid (CSF) rhinorrhea repair. Over the last decade, endoscopic surgery has established itself as the most widely used technique for the repair of CSF leak. Methods: 20 patients diagnosed with CSF rhinorrhea undergoing endoscopic CSF rhinorrhea repair were included in this study. To confirm the diagnosis beta-2 transferrin test was done. Accurate localization of site of lesion using CT cisternography was done. Results: Spontaneous onset of CSF rhinnorhea was noted in 75% of patients. The most common cause of CSF rhinorrhea in our study was spontaneous and the second most common cause was post traumatic. Almost 45% of patients presented with headache as primary complaint, 30% with only CSF leak, 20% with nasal obstruction and rest 5% with hyposmia. Conclusions: Multilayered closure of the dural defect was done. It can be concluded that middle aged people presented as CSF rhinorrhea with female predominance and there was high success rate of endoscopic CSF rhinorrhea repair with low morbidity.